Iliopsoas haematoma in a rugby player - Janse van Rensburg, D C (South African Journal of Sports Medicine, 2015)
Traumatic iliopsoas haematoma is a serious complication of haemorrhage disorders rarely seen in young healthy athletes. It is mostly described in patients on anticoagulant therapy and commonly associated with various degrees of femoral nerve palsy. A 22-year-old male rugby player presented with severe onset of pain in the lower back, right hip flexor/pelvic area following a tackle during a rugby match. Magnetic resonance imaging identified a distinct, hyperechoic heterogeneous mass within the right iliopsoas muscle, confirming a diagnosis of iliopsoas haematoma. The case resolved completely after conservative medical treatment in addition to a period of rest and intense active physical therapy. This case study reports the rare diagnosis of an uncomplicated iliopsoas haematoma following a sports injury in a young athlete.